Peran Pembelajaran Fiqih Wadhih terhadap Kualitas Ibadah Sholat Santri di TPQ Manbaul Hikmah 1 Wonoboyo Temanggung - Sofwan Chanan; Nurul Mubin; Ahmad Zuhdi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to examine the role of Fiqih Wadhih learning in improving the quality of students' prayer practices at TPQ Manbaul Hikmah 1 Wonoboyo, Temanggung. This research employs a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The results indicate that Fiqih Wadhih learning is systematically implemented using lecture, demonstration, memorization, and direct practice methods. Students gain a solid understanding of the requirements, pillars, and proper procedures of prayer. The routine of congregational prayers and a supportive environment contribute significantly to enhancing the students' prayer quality. However, differences in students' comprehension levels still exist, requiring more intensive guidance and reinforcement of prayer habits outside TPQ hours.